Do health care companies of India fulfil government's new orientation towards CSR activities: A special consideration towards maternal health - Shashi Lata Yadav; Babitha Vishwanath; Debasis Patnaik (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - Corporate social responsibility (CSR) in India includes education, environment, healthcare and rural development. In post-liberalized India, the healthcare sector (services and facilities) has grown in leaps and bounds over last two decades. The purpose of this paper is to reveal and explain the CSR profile of select healthcare companies of India and reveal gaps and scope of healthcare activities with a special consideration towards maternal health. Design/methodology/approach - Primary data are collected from seven listed companies of Goa state which were willing to participate in the study. In total, 67 companies constituting the Healthcare Sector Index of Standard & Poor of the Bombay Stock Exchange are considered as secondary source. Data of 59 companies that come within the threshold of Companies Act, 2013, are studied. CSR guidelines (with a turnover of Rs 10bn or a market capitalization of Rs 5bn or a net profit of Rs 50m) are taken as an initial frame of reference. Findings - In total, 89.83 per cent of these companies have initiatives related to health care. Structured companies (contribute to the company's overall mission and goals) with CSR policy have committee size varying from three to five directors with an independent director. During 2016-2017, they were mandated to spend Rs 4.2613bn out of which only 74.59 per cent was spent. Geographical spread of CSR initiatives is skewed, with majority of companies focussing on the states of Maharashtra and Gujarat, whereas the states of Odisha and North-Eastern being neglected. The focus areas of CSR are education, healthcare and rural development. The variation of MMR in different states of India is an indicator for corporate as to which state needs more attention. The corporate sector in India needs to focus on SDG3 target of MMR and move towards a newer dimension and direction. Originality/value - The originality of this paper lies in the recognition of the initiative of Government of India of weaning out CSR activities outside the purview of business sense and towards instilling a social sense in company behaviour. This is a dimensional and directional change in the evolution of CSR practices in companies and countries. To this end, 59 healthcare sector companies under the threshold of Companies Act 2013 were studied and results were outlined.